Malang soundloud community in strengthening the organization - Vania Devina Soekrisdo (Requisitoire Law Enforcement, 2021)
This study discusses the Malang Soundcloud Community in strengthening its organization by using the Soundcloud social media application. The purpose of this research is to find out and understand the Soundcloud Malang community in strengthening and maintaining its organization which only comes from overseas students who have the same interest in audiomusic. The benefit of this research is insight into knowledge about community organization systems that arise only from a common interest. This study uses the Leavitts Diamond concept from Harold J. Leavitt, with an organizational change approach that has four components, namely goals, social structure, members, and technology owned by the Soundcloud Malang community to maintain its community among the more diverse communities in Malang. Based on findings in the field, the background of the Malang Soundcloud Community was previously the Malang Poetry Night Community. The social structure in the organization in this case is to discipline or emphasize the existing rules in the organization. Members of the Malang Soundcloud Community are actors who play a role or are involved in this community. The Soundcloud Malang community uses social media applications to more easily share their work. And they made Kedai Robara a technology that bridges online and offline meetings.